What’s a chance event? Contrasting different senses of ‘chance’ with Aristotle’s idea of meaningful unusual accidents - Alexander Maar (Archai: Revista de Estudos sobre as Origens do Pensamento Ocidental, 2022)
In this article, I present and explain ten different possible meanings of a chance event – some ontological, some epistemic – and provide examples whenever possible. I describe and illustrate more carefully the view of chance (tychē) expressed by Aristotle in his Physics, a demanding and complex notion, and contrast it to the other senses examined. The etymology of chance also reveals a cross-reference between chance and indeterminism. I draw attention to the fact that most of the definitions of chance on offer need not conflict with causal determinism.